Life as we knew it - Pfeffer, Susan Beth, 1948- (Pfeffer, Susan Beth, 1948- Last survivors, 2006)
Through journal entries sixteen-year-old Miranda describes her family's struggle to survive after a meteor hits the moon, causing worldwide tsunamis, earthquakes, and volcanic eruptions.